A pragmatic evaluation of the role of the medial sural artery perforator flap - Hallock, Geoffrey G. (Journal of Xiangya Medicine, 2018)
The medial sural artery perforator (MSAP) flap is based on musculocutaneous perforators of the medial gastrocnemius muscle. A perforator within this region is routinely present. The flap has a potentially long vascular pedicle of large caliber which serves well to allow a local flap about the knee, or as a relatively thin free flap where vein grafts are rarely needed to reach a recipient site. Harvest of the flap is straightforward. Unfortunately, a skin graft if necessary to close the donor site or even a scar if primary closure were possible usually causes an unacceptable aesthetic residue. Choice of this donor site on this basis alone usually will make this only to be a secondary consideration.